KAPASITAS SIMPANAN AIR TANAH PADA SISTEM TATAGUNA LAHAN LPP TAHURA RAJA LELO BENGKULU - Edi Suharto (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2006)
Objective of this study was to measure soil water storage capacity on land use system at LPP TAHURA Raja Lelo Bengkulu. Research was conducted from September 1999 to February 2000 in Laboratory of soil of Agriculture Department, Gadjah Mada University. The Research used sampling design andanalysis the physics and chemistry of soils . Land use system was covered by tree crops which high of water storage capacity of soils. Those covered by grasses and scrub will be less. The variable of water storage capacity of soils are rain fall interception by vegetation of land cover, soil depth of root interception, the balanced of soil particle distribution of clays and sands, and the distribution of soil micro pore. Soil water drainage was determined by amount of organic matter in top soils. Therefore, forest and estate land use system covered by tree crops is an effective conventional landscape for soil and water conservation.